Pyloric duplication in the newborn: A rare cause of gastric outlet obstruction - Sinha C; Nour S; Fisher R (Wolters Kluwer Medknow Publications, 2007)
Pyloric duplication is the rarest duplication in gastrointestinal tract. Only seven cases have been reported so far in the English literature. In most cases pre-operative diagnosis was not made. We present such a case in a 9-day-old baby, presenting with non-bilious vomiting since birth. The diagnosis was made pre-operatively by ultrasonography, which is a good investigation for pre-operative diagnosis. The case was operated successfully without opening the pyloric canal.